Client-centred ADL intervention after stroke: Significant others' experiences. (September 2015) - Bertilsson, Ann-Sofie; von Koch, Lena; Tham, Kerstin; Johansson, Ulla
Abstract Background: Client-centredness is a prominent contemporary concept in rehabilitation. However, there is a lack of knowledge on if and how a client-centred rehabilitation approach is incorporated in the everyday life of significant others of people who receive such rehabilitation. Objective: Explore and describe if and how a client-centred ADL intervention (CADL) was integrated in the everyday lives of significant others of people with stroke. Materials and methods: Qualitative longitudinal design, with a grounded theory approach. Seven significant others, who cohabited with persons receiving a CADL intervention, were interviewed during the first year. Findings: One core category was identified: "Taking responsibility and achieving balance with respect to self-esteem in order to get on with everyday life". The integration of the CADL was a process. A key aspect was that as the person with stroke acted upon his/her own desired activity goals the significant others were encouraged to act on their own needs. Conclusions: Enablement is important also for the significant others of people with stroke. One way of enabling significant others to maintain an active lifestyle and find respite in everyday life might be to enable people with stroke to formulate and act upon their desired activity goals.